2012
DOI: 10.5511/plantbiotechnology.12.0215a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some therapies and meristem culture to eliminate Potato Y potyvirus from infected potato plants

Abstract: ). Finally, the highest percentage virus free plantlets of PVY (93% in Binella and 87% in Burren) were obtained from meristem-tips 100 µm in length excised a er electric treatments (15 mA/10 min).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 17 publications
0
18
0
3
Order By: Relevance
“…This procedure resulted in about 53% survival of the heat-treated shoots, 56% regeneration of shoot tips, and 91% and 74% of GLRaV-1- and GRSPaV-1-free plants. Thermotherapy followed by shoot tip culture was reported to eradicate PVY from infected potato [ 29 ]. In vitro virus-infected potato shoots were thermo-treated for 40 days at a consistent temperature of 37 °C, followed by shoot tip culture (0.1–0.3 mm).…”
Section: Thermotherapy-based Methods For Virus Eradicationmentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure resulted in about 53% survival of the heat-treated shoots, 56% regeneration of shoot tips, and 91% and 74% of GLRaV-1- and GRSPaV-1-free plants. Thermotherapy followed by shoot tip culture was reported to eradicate PVY from infected potato [ 29 ]. In vitro virus-infected potato shoots were thermo-treated for 40 days at a consistent temperature of 37 °C, followed by shoot tip culture (0.1–0.3 mm).…”
Section: Thermotherapy-based Methods For Virus Eradicationmentioning
confidence: 99%
“…In vitro virus-infected potato shoots were thermo-treated for 40 days at a consistent temperature of 37 °C, followed by shoot tip culture (0.1–0.3 mm). Culture of 0.1 mm shoot tips resulted in about 88% survival levels of the treated shoots and 75–81% virus-free plants in two potato cultivars, and larger shoot tips decreased the virus eradication frequencies [ 29 ].…”
Section: Thermotherapy-based Methods For Virus Eradicationmentioning
confidence: 99%
“…Effects of different antiviral chemicals including 2-thiouracil on PLRV elimination from In vitro-grown potato was reported and found that ribavirin and 2-thiouracil are effective for the production of potato virus free plantlets (Singh 2015). 2-thiouracil has also been used during virus elimination in plum plants and found that this antiviral drug has elimination capacity on plum pox virus (PPV) and a number of plants can be regenerated during eradication process (AlMaarri et al 2012;Jakab-Ilyefalvi et al 2012). Dithioracil can be combined with ribavirin for cymbidium mosaic virus elimination in dendrobium orchid (Katrina and Adelheid 1997).…”
Section: Antiviral Activity Of Other Antiviral Reagents For Eradicatingmentioning
confidence: 99%
“…Karena cara kerja khemoterapi adalah menghambat terjadinya replikasi virus, menghambat transport virus antarsel dan antar jaringan tanaman. Beberapa jenis bahan kimia antiviral banyak dimanfaatkan dalam kultur in vitro adalah analog sintetik dari guanosin, yaitu ribavirin (Al Maari, et al, 2012), dithiouracyl (Loythala et al, 2008) dan saat ini yang banyak dipakai adalah acycloguanin atau acyclovir. Acyclovir berfungsi sebagai antimetabolite yang dapat bersifat sebagai inhihibitor DNA Polymerase dari virus.…”
Section: Pendahuluanunclassified
“…Terlihat bahwa terdapat perbedaan panjang akar yang sangat berbeda nyata pada pemberian konsentrasi aniviral acyclovir yang semakin tinggi. Menurut (Al Maari et al, 2012) bahwa konsentrasi antiviral yang semakin tinggi akan mengakibatkan pertumbuhan yang melemah sebagai akibat dari kematian meristem atau penurunan metabolisme seluler pada tanaman inang. Pengaruh Waktu pemaparan Hasil uji beda nyata jujur (uji Tukey) taraf 5% menunjukkan bahwa perlakuan waktu pemaparan berpengaruh terhadap panjang akar tanaman,jumlah tunas, dan tinggi tanaman semakin lama waktu pemaparan maka semakin tinggi nilai panjang akar tanaman, jumlah tunas, dan tinggi tanaman(Gambar 5, 6, 7).…”
Section: Hasil Dan Pembahasan Pengaruh Interaksi Konsentrasi Antiviraunclassified